Internationalisation of Education and Competences Approach in the Digital World – Experts’ Opinions: A Round Table Debate Hosted by IRNet Project Researchers - Smyrnova-Trybulska, Eugenia; Kommers, Piet; Morze, Nataliia; Sekret, Iryna; Pavlova, Tatiana; Mokwa-Tarnowska, Iwona (International Journal of Research in E-learning, 2018)
The article focuses on the internationalisation of education and competences approach in the digital world as viewed by experts from different countries: the Netherlands, Poland, Turkey, Russia, and Ukraine. The article aims to provide opinions, views, and reflections on important topics addressed by the IRNet project and DLCC2017 Conference participants.